Molecular dynamics simulation of palmitate ester self-assembly with diclofenac - Karjiban, Roghayeh Abedi; Basri, Mahiran; Abdul Rahman, Mohd Basyaruddin; Salleh, Abu Bakar (MDPI, 2012)
Palm oil-based esters (POEs) are unsaturated and non-ionic esters with a great potential to act as chemical penetration enhancers and drug carriers for transdermal drug nano-delivery. A ratio of palmitate ester and nonionic Tween80 with and without diclofenac acid was chosen from an experimentally determined phase diagram. Molecular dynamics simulations were performed for selected compositions over a period of 15 ns. Both micelles showed a prolate-like shape, while adding the drug produced a more compact micellar structure. Our results proposed that the drug could behave as a co-surfactant in our simulated model.